An Overview of the Public Understanding of Islamic Banking in Mendahara Ilir - Akbar Marhafis, Muhammad; Daud; Haeran; Pitri, Alisyah; Kartika Devi, Erwina (CV. Civiliza Publishing, 2025)
This study aims to examine the level of public understanding of Islamic banking in Mendahara Ilir Village, Mendahara District, East Tanjung Jabung Regency, Jambi Province. Using a qualitative approach with a descriptive method, the study reveals that although the term